Parasite-Mediated Mate Preferences in a Cooperatively Breeding Rodent - Lutermann, Heike; Butler, Kemba B.; Bennett, Nigel C. (Frontiers in Ecology and Evolution, 2022)
Females of many species discriminate among males when choosing a mate and this can bear indirect and direct benefits including the avoidance of parasite transmission from infested males. In rodents, this may be mediated by androgen hormones that affect the expression of urinary odors. Female choosiness may also vary with a female’s infestation status, with infested females being less choosy. In the current study we tested the preference of cooperatively breeding highveld mole-rat (Cryptomys hottentotus hottentotus) females for male urinary odors from healthy males and those naturally infested with a cestode (Mathevotaenia sp.). Thirty females (15 healthy, 15 infested) were allowed to explore a Y-maze with urine samples from healthy and infested males and the frequency of entering choice arms and chambers and the duration spend with each odor sample was recorded. Infestation status did neither affect male body mass, urinary testosterone, nor cortisol levels or the body condition of females. Although overall female activity was not affected by infestation status, infested females entered choice arms and chambers significantly less frequently than healthy females. Surprisingly, healthy females preferred odors from infested males while the opposite was true for infested females, independent of male hormone levels. As the study species lives in groups that tend to share the same infestation status, we suggest that highveld mole-rat females may exhibit a preference for unfamiliar odors, possibly as an indicator of genetic diversity, rather than discriminate between infestation status of males. Similar mechanisms may also play a role in other social species.